THE REVEALING OF VIOLENCE TOWARDS SOCIAL ACTION IN ANIMATED FILM "ARCANE" BY CHRISTIAN LINKE & ALEX YEE - Teuku, Hazel Hafidzan Mauladani; Wahyuni (Prologue: Journal on Language and Literature, 2024)
This study explores on revealing violence towards social action in the animated film “Arcane” by Christian Linke and Alex Yee. There are two objectives of this research; 1) to find out how many types of violence that occur in the animated film “Arcane” by Christian Linke & Alex Yee and 2) how do the types of violence can reveal social actions in the animated film “Arcane” by Christian Linke & Alex Yee. The theory that has been used for this research is violence triangle by Johan Galtung, Weberian’s social action, and for the approach the researcher used sociology of literature; the methodology that is employed is descriptive qualitative research in which the researcher wanted to explain it much more detailedly. As for the data, they were collected from the screenplay and the script of the animated film. The result of this research is that the researcher found there are four kinds of types of violence which are direct violence, structural violence, and cultural violence. The revealing of social action that comes out after the appearance of violence serves as the response towards a particular act of violence.